Do Corporate Philanthropy, Leverage, and Company Size Affect The Financial Stability of Manufacturing Sector Companies on The Indonesia Stock Exchange? - Wijaya, Liliana; Gunawan, Andre; Sutejo, Bertha (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Manufacture sector becomes a focus of this research. The manufacturing sector was chosen because the sector had the biggest GDP in 2016-2020. This research aims to analyze the effect of corporate social responsibility based on corporate philanthropy, leverage, and firm size on the company's financial stability. Financial stability was used as a dependent variable in this study. This research uses a quantitative approach and multiple panel data regression method. The object used in this research was 456 observation data on the Indonesian Stock Exchange from 2016-2020. This research shows that corporate philanthropy has an insignificant effect on financial stability in Indonesia. Leverage has a significant negative effect on financial stability in Indonesia. Firm size has a significant positive effect on financial stability in Indonesia. The conclusion is that corporate philanthropy does not affect financial stability, while the level of leverage and the company's size affect financial stability. In Indonesia, the role of corporate philanthropy has not been as decisive as in developed countries. Managerial implications show that the company's size impacts customer trust so that the company has better governance. In addition, companies also need to properly manage the problem of using debt. It is within the optimal point limit not to become a burden and risk to the company. Keywords: corporate philanthropy, corporate social responsibility, financial stability, firm size, leverage